Lactobacillus rhamnosus and Xylo-oligosaccharides improve meat quality and modulate the microbiota composition of Magang geese aged 22-50 days - Ma, Y.; Luo, H.; Chen, J.; Chen, W.; Cao, Q.; Luo, X.; Lukuyu, Ben A.; Wang, S.; He, D.; Miao, K.; Jiang, X.; Saleemi, M.K.; et al. (Elsevier, 2026)
The evaluation of prebiotics and probiotics as additives for the enhancement of goose health and meat quality is still limited. The present study aimed to investigate the effects of Lactobacillus rhamnosus (LGG), xylo-oligosaccharides (XOS), and fructo-oligosaccharides (FOS) on growth performance, meat quality, and intestinal microbiota of Magang geese aged 22 to 50 days. A total of 720 22-day-old Magang geese were randomly assigned into four groups with six replicates of thirty geese per each. The control group was fed a basal diet, while the experimental groups were supplemented with 1 × 10¹⁰ cfu/kg LGG, 0.3 % XOS, and 0.4 % FOS respectively. The experiment lasted for 28 days. Our results indicated that these dietary 1 × 10¹⁰ cfu/kg LGG, 0.3 % XOS or 0.4 % FOS supplementation did not significantly alter growth performance of 22-50d Magang geese (P > 0.05). But thigh muscle yellowness in the XOS group was significantly higher than that in the CON group (P < 0.05), and muscle fiber density in the XOS group was lower than those in the CON and FOS groups (P < 0.05). LGG also decreased the cooking loss of breast muscle compared to the CON group (P < 0.05). Notably, LGG and XOS extremely increased the contents of C20:3n3, C24:1n9 and PUFA in thigh muscles of geese compared with those in CON and FOS groups (P < 0.01), suggesting an association between their supplementation and enhanced meat quality in geese. 16s rRNA sequencing analysis revealed that LGG supplementation increased Bifidobacterium (P = 0.0553), At the genus level, the populations of Lactobacillus (P = 0.0949) and Blautia (P < 0.05) were increased, while that of Romboutsia (P < 0.05) was decreased. Correlation analysis demonstrated strong associations between muscle fatty acid composition and specific bacterial taxa from Bacteroidota (e.g., Bacteroides and Alistipes) and Firmicutes (e.g., Peptostreptococcaceae and Faecalibacterium) (P < 0.01). In summary, while LGG, XOS, and FOS supplementation showed limited effects on goose growth, LGG and XOS significantly elevated thigh muscle PUFA content, underscoring their potential to enhance meat nutritional value through gut microbiota modulation.